2018
DOI: 10.1021/jacs.8b09848
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Gating of an Engineered Enzyme Captured in Real Time

Abstract: Enzyme engineering tends to focus on the design of active sites for the chemical steps, while the physical steps of the catalytic cycle are often overlooked. Tight binding of a substrate in an active site is beneficial for the chemical steps, whereas good accessibility benefits substrate binding and product release. Many enzymes control the accessibility of their active sites by molecular gates. Here we analyzed the dynamics of a molecular gate artificially introduced into an access tunnel of the most efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 58 publications
3
41
0
Order By: Relevance
“…This is consistent with the experimental finding that the rate-limiting step of the WT-catalyzed reaction is the release of BRE rather than Brrelease. 35 The WT enzyme also had the greatest number of BRE bound states, further supporting this conclusion.…”
Section: Molecular Dynamics Simulations and Markov State Modelssupporting
confidence: 54%
See 2 more Smart Citations
“…This is consistent with the experimental finding that the rate-limiting step of the WT-catalyzed reaction is the release of BRE rather than Brrelease. 35 The WT enzyme also had the greatest number of BRE bound states, further supporting this conclusion.…”
Section: Molecular Dynamics Simulations and Markov State Modelssupporting
confidence: 54%
“…We have previously shown that L177W undergoes slow conformational changes between open and closed states and that it is difficult for Brto exit from the closed conformation. 35 W140A/F143L/L177W/I211L displays similar conformational dynamics but over shorter time scales. When DBE is bound to the p3 tunnel or the active site, it forms favorable lipophilic interactions with the surrounding residues, reducing the likelihood that the protein will go from the closed to the open state.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Disturbing the transport of ligands into and out of the active site by blocking the main tunnel with a bulky Trp residue (L177W) unexpectedly caused strong SI. 35,36 To investigate this effect, a new variant (LinBW140A/F143L/L177W/I211L) bearing three further mutations was generated. These three mutations opened an auxiliary access tunnel to the active site, modified the dynamics of the main tunnel, and restored the level of SI to that observed in the wild type.…”
Section: Introductionmentioning
confidence: 99%
“…In ligand binding and unbinding events, especially when the binding site is deeply buried in the protein structure, ligands often have to travel tens of angstroms. Such a transport process requires a series of systematic adjustments of protein side-chains and backbones along the traversed paths that might take up hundreds of milliseconds to occur [26]. Among the slowest principal motions performed by proteins are highly organized collective translocations of whole domains, starting on microsecond timescales and with amplitudes reaching nanometers.…”
Section: Introductionmentioning
confidence: 99%